Stage IV renal cell carcinoma achieves pathologic complete response after two ipilimumab plus nivolumab courses despite severe immune-related adverse events: a case report - Ryo Takada; Miki Fujiwara; Masatoshi Maki; Naoyuki Nomura; Shintaro Kono; Akira Fujita; Hiroshi Masumoto; Yoko Takahashi; Yasuhisa Hasegawa; Koji Tamura (BMC, 2024)
Abstract Background Ipilimumab (Ipi) plus nivolumab (Nivo) is the recommended first-line treatment for renal cell carcinoma (RCC). This report describes a case where pancreatic metastases disappeared after only two courses of Ipi + Nivo therapy. The primary tumor was cured by surgery, and a pathological Complete Response (pCR) was observed despite multiple serious immune-related Adverse Events (irAEs). Case presentation A 54-year-old woman with RCC and pancreatic metastasis at stage IV, diagnosed with intermediate risk according to the International Metastatic RCC Database Consortium classification, underwent initiation of Ipi + Nivo therapy. On day 26, she developed hyperthyroidism accompanied by tachycardia, leading to the commencement of metoprolol tartrate treatment. Following the resolution of tachycardia, a second course of Ipi + Nivo therapy was administered on day 50. By day 70, the patient exhibited Grade 3 hepatic dysfunction, followed by the onset of hypothyroidism on day 75, necessitating treatment with steroids and levothyroxine. After positive treatment, a Grade 3 skin disorder emerged on day 87 while tapering steroids, prompting treatment with methylprednisolone (mPSL) pulse therapy. The skin disorder responded to steroids, allowing for tapering. However, on day 113, a recurrence of Grade 3 skin disorder occurred, necessitating another mPSL pulse. The patient responded well to treatment, exhibiting improvement in her condition. On day 131, she presented at the hospital with complaints of respiratory distress, prompting a Computed Tomography (CT) scan that revealed interstitial pneumonia. By day 272, subsequent CT imaging showed the disappearance of pancreatic metastasis and shrinkage of the primary tumor. On day 294, she underwent a laparoscopic left nephrectomy. Pathological analysis confirmed a pCR in the primary tumor, indicating successful eradication of RCC through surgical intervention. Conclusions This case report presents a scenario where multiple severe irAEs appeared in a patient, yet metastases disappeared after only two courses of Ipi + Nivo therapy. The patient was ultimately cured by surgery and achieved a pCR. This case highlights that despite the occurrence of severe irAEs during RCC treatment with Ipi + Nivo therapy, they can be managed appropriately to maximize the therapeutic effects of checkpoint inhibitors.